2019
DOI: 10.1093/mnras/stz1401
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of great magnetic storms on 6–8 March 1582

Abstract: Although knowing the occurrence frequency of severe space weather events is important for a modern society, it is insufficiently known due to the lack of magnetic or sunspot observations, before the Carrington event in 1859 known as one of the largest events during the last two centuries. Here, we show that a severe magnetic storm occurred on 8 March 1582 based on auroral records in East Asia. The equatorward boundary of auroral visibility reached 28.8° magnetic latitude. The equatorward boundary of the aurora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…Hattori et al (2019), based on auroral records in East Asia, estimated that this severe storm occurred on 8 March 1582 and was comparable with other more recent magnetic storms as, for example, those in 1909 (Hayakawa et al, 2019a) and 1989 (Allen et al, 1989). Hattori et al (2019) also indicated that the duration of this storm could be three days. Very few records from South Europe are available for this event.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Hattori et al (2019), based on auroral records in East Asia, estimated that this severe storm occurred on 8 March 1582 and was comparable with other more recent magnetic storms as, for example, those in 1909 (Hayakawa et al, 2019a) and 1989 (Allen et al, 1989). Hattori et al (2019) also indicated that the duration of this storm could be three days. Very few records from South Europe are available for this event.…”
Section: Introductionmentioning
confidence: 53%
“…According to both documentary sources reported in this work, the aurora observed in March 1582 was sighted in Lisbon. Figure 1 depicts the European places where aurora was recorded according to Hattori et al (2019) in addition to the records made in Lisbon reported here. It implies that the records made in Lisbon were the southernmost observation recorded in Europe about the aurora of 1582.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 3 more Smart Citations